DAMPAK KEPUASAN KERJA TERHADAP KINERJA KARYAWAN YANG DIPENGARUHI VARIABEL KOMPENSASI MONETER DAN HUMAN RELATION PADA UD. CERIA ABADI - Galih Panjalu Pramono; Endah Winarti HS (LPPM STIE DHARMAPUTRA SEMARANG, 2022)
ABSTRACTThe purpose of this study was to determine the effect of monetary compensation and human relations on job satisfaction and its implications for the performance of UD employees. Eternal Prosperity. The population studied was 55 people. With a sample of all members of the population with the census method. This research uses multiple regression analysis technique. The results of hypothesis testing show that monetary compensation has a positive and significant on job satisfaction, so hypothesis 1 (H1) is approved. The result hypothesis 2 (H2) is Human relations has a positive and significant on job satisfaction, so hypothesis 2 (H2) is approved. The result hypothesis 3 (H3) is Job satisfaction has a positive and significant on employee performance, so hypothesis 3 (H3) is approved. Based on the results of this study, UD. Ceria Abadi to pay more attention to monetary compensation and human relations in order to increase job satisfaction so that performance can be maximized. Keywords: monetary compensation, human relations, job satisfaction, employee performance. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui Pengaruh kompensasi moneter dan human relation terhadap kepuasan kerja serta implikasinya terhadap kinerja karyawan UD. Ceria Abadi. Populasi yang diteliti sebanyak 55 orang. Dengan sampel seluruh anggota populasi dengan metode sensus. Penelitian ini menggunakan teknis analisis regresi berganda. Hasil pengujian hipotesis didapat bahwa kompensasi moneter berpengaruh positif signifikan terhadap kepuasan kerja, sehingga hipotesis 1 (H1) terbukti. Hasil pengujian hipotesis 2 (H2) menunjukkan Human relations berpengaruh positif signifikan terhadap kepuasan kerja, sehingga hipotesis 2 (H2) terbukti. Pengujian hipotesis 3 (H3) menunjukkan kepuasan kerja berpengaruh positif signifikan terhadap kinerja karyawan, sehingga hipotesis 3 (H3) terbukti. Berdasarkan hasil penelitian ini, UD. Ceria Abadi agar lebih memperhatikan kompensasi moneter dan human relation agar dapat meningkatkan kepuasan kerja sehingga kinerja bisa lebih optimal. Kata kunci: kompensasi moneter, human relation, kepuasan kerja, kinerja karyawan